Host plants of fruit flies (Diptera: Tephritidae) in Morocco - El Harym, Younes; Belqat, Boutaïna; Norrbom, Allen (Zootaxa, 2022)
A list of 128 host plant species of Tephritidae from Morocco is provided. Of these plants, 34 are reported for the first time as hosts for Tephritidae in Morocco, while 41 taxa are newly discovered hosts for Tephritidae globally. Six species are confirmed as host plants. A total of 41 species of Tephritidae were reared from flowers, flower heads, galls, or fleshy fruits collected in the field and brought to the laboratory for rearing. For these tephritid species, the host plants in Morocco were studied for the first time. Illustrations of some endemic host plant species are also provided.